ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KEPUASAN PASIEN DI RSU ROYAL PRIMA MEDAN - M. Iqbal; Ali Mahadi Ritonga, Angga Pradana Kusuma, Nanda Kurniawan Lubis (CV. ADIBA AISHA AMIRA, 2024)
This mini-research aims to analyze the influence of fairness on patient satisfaction in the inpatient room at RSU Royal Prima Medan. This research uses a quantitative approach with a cross-sectional survey design. In this research, researchers used questionnaires collected from respondents as a source of information to analyze the influence between the concept of Good Corporate Governance and patient satisfaction, through approach, observation and data collection at the same time. The research is located at RSU Royal Prima Medan. Research findingsshow 1) Fairness has an impact on patient satisfaction at RSU Royal Prima Medan. hospital inpatient room; (2) Transparency has an impact on patient satisfaction in hospital inpatientrooms; (3) Accountability has an impact on patient satisfaction in hospital inpatient rooms; (4) Responsibility influences the degree of patient satisfaction in the inpatient room at RSU Royal Prima Medan; and (5) The dominant justice variable influences patient satisfaction at RSU Royal Prima Medan